The Role of Christian Books in the Faith Formation of the GMIM Baitel Eris Congregation: Peran Buku Kristen dalam Pembentukan Iman Jemaat Gmim Baitel Eris - Kevia N.V. Kamu; Filipi Syelomita Tololiu; Zheruya Seidy Grasella Wentinusa; Christofanny Londa; Evi Stans Evlin Tumiwa; Hendry C. M. Runtuwene; Rivay Palempung; Ramli Sarimbangun (Santhet: (Jurnal Sejarah, Pendidikan Dan Humaniora), 2025)
This study examines how the Christian book, the Buku Renungan Harian Keluarga (RHK), influenced the formation of faith among the members of GMIM Baitel Eris in the Tandengan District. Set in the context of the overall discussion on Protestant spiritual formation and family worship, the study deals with the current application of RHK in home worship, its perception by congregants, and its contribution to spiritual development and family life. Data were collected using a qualitative case study design, where semi-structured interviews with adult congregants, parents, youth, Sunday school teachers, column leaders, and office-bearers of the church were used, supplemented by participatory observations during family and sectoral worship venues and document analysis of RHK editions and church records. Thematic data analysis was conducted in accordance with the steps of data analysis presented by Braun and Clarke. The results indicate that RHK is more strongly integrated into GMIM Baitel Eris' daily piety, and thus, it is a domestic liturgical script that reflects congregational worship. The devotional reflection part is the experience that is found to be the most valuable, as it connects Scripture and everyday life. According to the respondents, they experienced improved spiritual knowledge, increased intimacy with God, self-character development, and improved family relations. The first barrier to regular use was busyness, and the digital formats and proposed interactive features are hints of what needs to be changed in the future. The paper concludes that Christian books continue to play a crucial role in the formation of faith in local GMIM settings and makes pastoral suggestions to support and revitalise the practices of family-oriented devotion in the face of modern-day social and technological transformation.